Frontispiece: Intramolecular Electric Field Construction in Metal Phthalocyanine as Dopant‐Free Hole Transporting Material for Stable Perovskite Solar Cells with >21 % Efficiency. Issue 12 (8th March 2021) - Yu, Zefeng; Wang, Luyao; Mu, Xijiao; Chen, Chun‐Chao; Wu, Yiying; Cao, Jing; Tang, Yu
Abstract : Perovskite Solar Cells In their Communication on page 6294, Jing Cao et al. report the preparation of a nickel phthalocyanine decorated with four methoxyethoxy units and its application as a hole‐transporting material in perovskite solar cells.